Hepatic patch by stacking patient-specific liver progenitor cell sheets formed on multiscale electrospun fibers promotes regenerative therapy for liver injury. (July 2021) - Kim, Yohan; Kim, Young Won; Lee, Seung Bum; Kang, Kyojin; Yoon, Sangtae; Choi, Dongho; Park, Suk-Hee; Jeong, Jaemin
Abstract: Recently, use of cell sheets with bio-applicable fabrication materials for transplantation has been an attractive approach for the treatment of patients with liver failure. However, renewable and scalable cell sources for engineered tissue patches remain limited. We previously reported a new type of proliferating bipotent human chemically derived hepatic progenitor cells (hCdHs) developed by small molecule-mediated reprogramming. Here, we developed a patient-specific hepatic cell sheet constructed from liver biopsy-derived hCdHs on a multiscale fibrous scaffold by combining electrospinning and three-dimensional printing. Analysis of biomaterial composition revealed that the high-density electrospun sheet was superior in increasing the functional properties of hCdHs. Furthermore, the hepatic patch assembled by multilayer stacking with alternate cell sheets of hCdHs and human umbilical vein endothelial cells (HUVECs) recapitulated a liver tissue-like structure, with histological and morphological shape and size similar to those of primary human hepatocytes, and exhibited a significant increase in hepatic functions such as albumin secretion and activity of cytochrome P450 during in vitro hepatic differentiation compared with that in hCdH cells cultured in a two-dimensional monolayer. Interestingly, in the hepatic patch, the induction of functional hepatocytes was associated with both the electrospun fibrous-facilitated oncostatin M signaling and selective activation of AKT signaling by HUVECs. Notably, upon transplantation into a mouse model of therapeutic liver repopulation, the hepatic patch effectively repopulated the damaged parenchyma and induced the restoration of liver function with healthy morphology in the lobe and an improved survival rate (>70%) in mice. Overall, these results suggested that liver biopsy-derived hCdHs can be an efficient alternative source for developing hepatic cell sheets and patches with potential clinical applications in tissue engineering to advance liver regeneration.